Eletrodo de pasta de carbono modificado com ftalocianinade cobalto para determinação de carbenzim em laranjas - Severo, Flaviana Justino Rolim (2018)
Pesticides are widely used to control agricultural pests, ensuring productivity in the industry worldwide. In this context, carbendazim (MBC) methyl benzimidazol-2-yl carbamate, a systemic fungicide, toxicological class III, is among the most used for citrus cultivation, and has foliar application regulated in Brazil by ANVISA, which establishes as acceptable daily intake IDA) the maximum value of 0.02 mg kg-1 MBC in relation to body weight. The determination of MBC can be done directly in the electrochemical cell, with minimal steps of treatment of the sample. Thus, in this work, a carbon paste electrode modified with cobalt phthalocyanine was made for determination of carbenzim in oranges. The preparation of the electrode involved the mixing of graphite powder, mineral oil and cobalt phthalocyanine in different percentages. The samples of oranges were collected at local supermarkets in the city of João Pessoa - PB. The voltammetric techniques used were cyclic (VC) and square wave (VOQ) voltammetry. The studies were performed in potentiostat / galvanostat model PGSTART® 302N Metrohm, electrolyte support buffer Briton Robson (BR) pH 4.5 and Ag / AgCl electrodes and platinum wire as reference and auxiliary respectively. For the analytical curve, the linearity range obtained was 95.11 to 667.9 µg L-1, R2 = 0.9987, with detection limits of 12.0 µg L-1 and 40.1 µg L-1 for limit of quantification, respectively. The accuracy studies showed recovery values of 102% and 93.8% and 98.2% of MBC, considered in the allowed range (70 to 120%). This work is pioneer in the electrochemical oxidation studies of MBC on EPC-CoPC. The electrode is simple to make, easy renovation of the surface low cost. The study of the percentage of EPC-CoPC as the carbon paste modifying agent indicated that the best percentage was 1% CoPC. The use of EPC-CoPC for the determination of MBC in oranges demonstrated applicability for the studied samples, with the advantage of using simplified and low-cost instrumentation for both acquisition and maintenance, rapid analytical response, high sensitivity, promising for application in other food matrices.